Towards a Political Ecology of Food Security and Sustainability in Nigeria - Okoli, Al Chukwuma; Tedheke, Moses (NIU Journal of Humanities, 2018)
The concern of food security and sustainability constitutes an integral part of Nigeria’s contemporary national security problematic. This paper explores the food security and sustainability discourse in Nigeria within the paradigm of political ecology with a view to situating the notions and nuances that are associated therewith. By means of a discursive analysis, predicated on secondary data, the paper x-rays the socio-structural issues underlying food security as well as food vulnerability in Nigeria, positing that Nigeria’s quest for food security/sustainability has been vitiated by a myriad of complex social, political, ecological and developmental factors negating food availability, access, safety and sustainability. The paper submits that these factors must be organically understood and addressed in order to overcome the threat of food insecurity/crisis in Nigeria.